The Principle of Balance as an Instrument of Judicial Correction in the Collective Agreement on Industrial Relations - Nurshoim Ramadhan Putra; Atik Winanti; Irwan Joesoef (Journal of Law Perspectives Review, 2026)
A Settlement Agreement is one of the legal instruments for resolving industrial relations disputes and becomes legally binding after being registered with the Industrial Relations Court. In practice, however, not all Settlement Agreements are concluded through negotiations that reflect an equal bargaining position between the parties. The imbalance of bargaining power between employers and employees often gives rise to abuse of circumstances , which may affect the substantive validity of the agreement. This study aims to analyze the legal validity of Settlement Agreements resulting from unequal bargaining positions and to examine the role of the Principle of Balance as an instrument of judicial correction in industrial relations dispute resolution. This research employed a normative legal research method using both the statutory approach and the case approach. The legal materials consisted of primary, secondary, and tertiary legal sources collected through library research and analyzed using a qualitative prescriptive method. The findings indicate that the binding force of a Settlement Agreement is determined not only by the fulfillment of formal legal requirements but also by the substantive requirements stipulated in Article 1320 of the Indonesian Civil Code. A Settlement Agreement concluded under abuse of circumstances may lack substantive validity because it does not reflect genuine consent. The study further finds that the Principle of Balance serves as a legal basis for judges to exercise judicial correction by disregarding exploitative contractual clauses without invalidating the entire agreement. This approach provides greater protection for employees' statutory rights while maintaining legal certainty and promoting substantive justice in the settlement of industrial relations disputes